Combination a Skeleton Filter and Reduction Dimension of Kernel PCA Based on Palmprint Recognition - Muhammad Kusban; Adhi Susanto; Oyas Wahyunggoro (Institute of Advanced Engineering and Science, 2016)
Palmprint identification is part of biometric recognition, which attracted many researchers, especially when fusion with face identification that will be applied in the airport to hasten knowing individual identity. To accelerate the process of verification feature palms, dimension reduction method is the dominant technique to extract the feature information of palms.The mechanism will boost if the ROI images are processed prior to get normalize image enhancement.In this paper with three sample input database, a kernel PCA method used as a dimension reduction compared with three others and a skeleton filter used as a image enhancement method compared with six others. The final results show that the proposed method successfully achieve the target in terms of the processing time of 0.7415 second, the EER performance rate of 0.19 % and the success of verification process about 99,82 %.